2012
DOI: 10.1159/000338133
|View full text |Cite
|
Sign up to set email alerts
|

Single Umbilical Artery: Does Side Matter?

Abstract: Introduction: The aim of this study was to determine if laterality of an absent umbilical artery (AUA) is associated with specific sonographic findings, chromosomal defects or postpartum birth defects. Materials and Methods: In this retrospective cohort study, ultrasound reports and medical records of patients who received an obstetric ultrasound at the University of Iowa Hospitals and Clinics with an identified laterality of the AUA from 1989 to 2007 (n = 405) were reviewed. Rates of sonographic abnormalities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
1
7
0
1
Order By: Relevance
“…Similar finding was noted by Fujikura [25]. (1984), and Santillan et al [26], (2002), but Bourke et al [14], Geipel et al [22], (2000) and Marie et al Heifet [7], (2009) found that the incidence of a SUA is more common in females than in males.…”
Section: Resultssupporting
confidence: 73%
“…Similar finding was noted by Fujikura [25]. (1984), and Santillan et al [26], (2002), but Bourke et al [14], Geipel et al [22], (2000) and Marie et al Heifet [7], (2009) found that the incidence of a SUA is more common in females than in males.…”
Section: Resultssupporting
confidence: 73%
“…In human medicine, the anomaly of the UA is well documented and it is called ‘single umbilical artery’. Diagnosis of this anomaly is important to evaluate together with some others congenital malformations (Johnson and Tennenbaum, ; Pomeranz, ; Murphy‐Kaulbeck et al., ; Kondi‐Pafiti et al., ; Santillan et al., ; Tasha et al., ). Even though such anomalies have not been described in veterinary medicine in detail, animal's models have been used to study the presumptive relationship between the presence of single umbilical artery and organ malformations (Merei, ).…”
Section: Discussionmentioning
confidence: 99%
“…There are three theories concerning the pathogenesis of an absent umbilical artery: (i) primary agenesis; (ii) secondary atrophy or atresia of the previously normally developed vessel; and (iii) persistence of the original allantoic artery of the body stalk . Since it was first reported, the SUA has attracted special attention from obstetricians because of the high incidence of complications in infants with SUAs, such as multiple malformations or chromosome abnormalities . An isolated SUA (ISUA) occurs with no complications of congenital abnormality in fetal chromosomes or structure; approximately 80% of SUAs are ISUAs.…”
Section: Introductionmentioning
confidence: 99%
“…1 Since it was first reported, the SUA has attracted special attention from obstetricians because of the high incidence of complications in infants with SUAs, such as multiple malformations or chromosome abnormalities. [2][3][4] An isolated SUA (ISUA) occurs with no complications of congenital abnormality in fetal chromosomes or structure; approximately 80% of SUAs are ISUAs. However, up-to-date studies on SUAs mostly focus on fetal congenital abnormalities or perinatal mortalities; studies on pregnancy outcome and delivery modes for infants with ISUAs are rare, especially in live, full-term births.…”
Section: Introductionmentioning
confidence: 99%